SBA‐15‐supported N‐coordinate ruthenium(II) materials bearing sulfonamide‐type ligands: Effect of ligand backbones on catalytic transfer hydrogenation of ketones and aldehydes. (20th January 2017) - Dayan, Serkan; Kayaci, Nilgun; Kalaycioglu Ozpozan, Nilgun; Dayan, Osman
Abstract : [RuLCl( p ‐cymene)] (L = N ‐arylsulfonylphenylenediamine) complexes (2 a –d ) were synthesized from the reaction between [Ru( p ‐cymene)Cl2 ]2 and ligand. Additionally, SBA‐15–[RuLCl( p ‐cymene)] derived catalysts (3 a –d ) were successfully immobilized onto mesoporous silica (SBA‐15) by an easily accessible approach. The structural elucidations of2 a –d and3 a –d were carried out with various methods such as 1 H NMR, 13 C NMR and infrared spectroscopies, elemental analysis, thermogravimetric/differential thermal analysis, nitrogen adsorption–desorption and scanning electron microscopy/energy‐dispersive X‐ray analysis. The Ru(II) complexes and materials were found to be highly active and selective catalysts for the transfer hydrogenation (TH) reaction of aldehydes and ketones. The influence of various 1, 2‐phenylenediamines on the reactivity of the catalysts (complexes or materials) was studied and the catalysts (2 d and3 d ) with a 4, 5‐dichlorophenylenediamine substituent showed the best activity (the maximum turnover frequencies are 2916 and 2154 h −1 for TH of 4‐fluoroacetophenone, and 6000 and 4956 h −1 for TH of 4‐chlorobenzaldehyde). Abstract : Ruthenium(II) complexes and supported complexes were prepared from N‐arylsulfonylphenylenediamines. They were used as catalysts in transfer hydrogenation of acetophenone derivatives and aromatic aldehydes.